Sea of Cortez expedition. - unknown:::Creator:::
The Western Flyer docked before the Sea of Cortez trip departure. A Man and two women are looking over the edge of boat. Ed 'Doc' Ricketts in dark shirt, Ritzi 'Tiny' Colletto in light shirt. All have their backs to viewer. Sea of Cortez expedition.